Satan and Lucifer: a comparison of their metamorphoses from Angel to Devil in Milton's Paradise lost and Vondel's Lucifer and Adam in Ballingschap - Paterson, Lynette (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1979)
The aim of this thesis is to compare the poetic delineation of the character of Satan in Paradise Lost with that of Lucifer in Lucifer and Adam in Ballingschap, and to consider the influence of the genre in each case , not in order to prove similarities or differences , but rather to allow the characters to illuminate each other. Both Satan and Lucifer develop progressively from angel to devil in the course of the poem or play. However, this process is more than just a physical metamorphosis, or even a moral degeneration. It is in each case a process of identity change, intensely and consciously experienced by the character. The fall is a movement from God to Self. The unfallen creature's integrity consists in his submergence in the Being and Will of God; for the fallen creature integrity means a separate, independent self-hood. In rebelling against their role and duty as Archangel, Satan and Lucifer rebel against submergence in the Being of God and thus against their very nature and the order of things. Consequently they experience personal and psychological disintegration. From this condition of imbalance and uncertainty they both develop to a new state of personal reintegration and unequivocal identity, now as Arch-fiend. In neither case is the process instant or entirely concurrent with the physical fall into Hell. Rather, it is protracted, hence the division of this thesis into sections that focus on the different stages in the development: Archangel, Arch-rebel and Arch- fiend (introduction, p. ii-iii).
Keywords: Milton, John, 1608-1674; Vondel, Joost van den, 1587-1679